Implementation of Pancasila Values on the Character of Environmental Concern in the Life of Islamic Boarding Schools - Savitri, Yulia Ayu (Universitas Negeri Semarang, 2016)
The living environment is the human habitation of everyday life. As the successor generation of the nation, must be embedded values Pancasila high environmental social concern. Environmental conditions have an effect on everyday activities. In addition, the implementation of Pancasila values is very important for the environmental conservation of Pesantren. The common problem is the lack of awareness of environmental hygiene resulting in the onset of viral diseases. Not only that, lack of control and supervision of the caretaker Pondok Pesantren also affects. Diseases that attack are usually mild diseases, such as flu, fever, and others. But there are also infectious diseases and causes of death. From this problem, students who have infectious diseases will be difficult to overcome. Because students ' life is identic with togetherness or interdependence with one another. The method used is a qualitative approach by using stages of observation, observation, interviews. This Model of research is not only to analyse internal life in the cottage environment, but also the life of an extense involving problems in the cottage environment. From this research obtained the result that it takes socialization or appeal for students to maintain the environment by raising awareness of the importance of clean and healthy environment. And provide information about the variety of creativity that can be utilized for items that are not used.